2006
DOI: 10.1093/jxb/erl182
|View full text |Cite
|
Sign up to set email alerts
|

An early auxin-responsive Aux/IAA gene from wheat (Triticum aestivum) is induced by epibrassinolide and differentially regulated by light and calcium

Abstract: The plant hormone auxin plays a central role in regulating many aspects of plant growth and development. This largely occurs as a consequence of changes in gene expression. The Aux/IAA genes are best characterized among the early auxin-responsive genes, which encode short-lived transcriptional repressors. In most plants examined, including Arabidopsis, soybean, and rice, the Aux/IAA genes constitute a large gene family. By screening the available databases, at least 15 expressed sequence tags (ESTs) have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 52 publications
6
34
0
Order By: Relevance
“…In a manner similar to that already demonstrated for orthologous genes in rice (Oryza sativa; Song et al, 2009) and wheat (Singla et al, 2006), we found that BR application to Arabidopsis seedlings increased the expression of IAA1 in Ws-2 wildtype plants (Fig. 6).…”
Section: Ca 2+ Signaling and Br-dependent Gene Expressionsupporting
confidence: 83%
See 2 more Smart Citations
“…In a manner similar to that already demonstrated for orthologous genes in rice (Oryza sativa; Song et al, 2009) and wheat (Singla et al, 2006), we found that BR application to Arabidopsis seedlings increased the expression of IAA1 in Ws-2 wildtype plants (Fig. 6).…”
Section: Ca 2+ Signaling and Br-dependent Gene Expressionsupporting
confidence: 83%
“…( Fig. 7), a gene known to be responsive to BR (Singla et al, 2006;Song et al, 2009). Further experiments examining IAA1 expression are consistent with this model (Fig.…”
Section: Ca 2+ Signaling and Br-dependent Gene Expressionsupporting
confidence: 71%
See 1 more Smart Citation
“…Vert et al (2008) studied synergistic interactions of BRs and auxins and reported integration of auxins and brassinosteriod pathways by auxins response factors responsible for synergism between BRs and auxins. Elevated expression of TaIAA1 gene of Aux/IAA gene family on application of 24-epiBL in wheat was also recorded (Singla et al, 2006). Similarly, the stress protective role of auxins against heavy metals was also observed by Dimpka et al (2008) in Streptomyces spp.…”
Section: Discussionmentioning
confidence: 54%
“…Kraepiel et al (1995) indicated that the isoforms of light-expressed phytochrome controlled the endogenous indole-3-acetic acid (IAA) level of calli in Nicotiana plumbaginifolia. Results of recent studies suggest the existence of cross-talk between auxin and light signaling (Salisbury et al 2007, Sibout et al 2006, Singla et al 2006. On the other hand, Bangerth (2001a, 2001b) indicated that endogenous hormone levels differed depending on the competence of calli; embryogenic calli showed higher IAA and lower cytokinin than non-embryogenic calli.…”
Section: Introductionmentioning
confidence: 98%